Speed-sensorless Control of DFIG in the Condition of LVRT - SHE Yue; SHENG Jianke; ZHANG Shaoyun; XU Fengxing (Kongzhi Yu Xinxi Jishu)
It presented a speed-sensorless control method of DFIG to adapt to LVRT operation condition. Firstly, a DFIG vector control model based on stator coordinate and rotator coordinate was given, characteristics of rotor voltage in normal working condition and LVRT condition were analyzed, and feature of proportional integral resonant controller (PIR) was introduced. Thus it obtained a control strategy of rotor side converter that should be taken in LVRT condition. In order to decrease error band of the estimated rotor speed in LVRT condition, a close-loop adaptive controller based on PIR instead of PI was proposed to use in the method of speed identification of DFIG which based on the model reference adaptive system on the basis of rotor current. To verify the correctness of theoretical analysis, 2.5 MW DFIG was used as an example to establish a simulation model. Simulation results show that, both in normal operation and LVRT conditions, estimated rotor position can track the actual value accurately in different speeds and powers, which can insure the accuracy of active / reactive power control, and the feasibility of this scheme is feasible.